Privacy Concerns and Acceptance of Government Surveillance in Australia - Thompson, Nik; Bunn, Anna; Kininmonth, Joel; McGill, Tanya (2018)
Increases in routine data collection and surveillance in recent years have resulted in ongoing tension between citizens’ privacy concerns, perceived need for government surveillance and acceptance of policies. We address the lack of Australia focussed research through an online survey of 100 Australian residents. Data was analysed using PLS, revealing that privacy concerns around collection influence acceptance of surveillance but do not influence enactment of privacy protections. Conversely, respondents’ concerns about secondary use of data were unrelated to their levels of acceptance, yet were a significant determinant of privacy protections. These findings suggest that respondents conflate surveillance with collection of data, and may not consider subsequent secondary use. This highlights the multi-dimensional nature of privacy which must be studied at sufficiently granular level to draw meaningful conclusions. Our research also considers the role of trust in government, and perceived need for surveillance and these findings are discussed with their implications.